СЕРДЦЕ В ОСЬМИНОЖЬЕЙ ЛОВУШКЕ - Г. П. Арутюнов; Н. В. Хохлова; Н. А. Былова; А. С. Тюхтина (SINAPS LLC, 2013)
Tako-tsubo cardiomyopathy, also known as stress-induced cardiomyopathy or transient apical ballooning syndrome, is a distinctive reversible condition often affecting postmenopausal women after a stressful event. It is characterized by sudden temporary systolic dysfunction of the apical and/or midsegments of the left ventricle. The goal of this article is to review the actual knowledge about Tako-tsubo to help the general practitioner. We also presented the case of a 47-year-old woman victim of a tako-tsubo syndrome with delirium in first hours of the desease.